Reconstructing Contextual Educational Leadership Based on Local Wisdom Values - Rahmania Rahman; Burhan Burhan; Muhammad Fuad; Abdul Munir HB (ITEKES Permata Ilmu Maros, 2025)
This article presents a theoretical reconstruction of educational leadership through the integration of local wisdom values using a qualitative literature study approach. The background of this study lies in the dominance of universal leadership models that tend to marginalize socio-cultural contexts, resulting in educational leadership practices that are less adaptive and less meaningful in local settings. This condition indicates the need for a reorientation of educational leadership toward a contextual and culturally grounded paradigm, particularly in multicultural societies such as Indonesia. This study employs a qualitative literature review by analyzing national and international journal articles and academic books published within the last ten years that discuss educational leadership and local wisdom. Data were analyzed using content analysis and thematic analysis to identify conceptual patterns, core values, and leadership practices that reflect local wisdom. The findings reveal that local wisdom values such as gotong royong, musyawarah, exemplary leadership, social harmony, and environmental awareness constitute a strategic foundation for reconstructing educational leadership that is contextual, humanistic, and participatory. The integration of these values strengthens school culture, enhances teacher performance and discipline, promotes participatory decision-making, and reinforces school–community relations. This study concludes that reconstructing educational leadership based on local wisdom not only enriches leadership theory with cultural and contextual dimensions but also provides a sustainable alternative framework for educational leadership practices in Indonesia.